2012
DOI: 10.1088/0004-637x/751/1/29
|View full text |Cite
|
Sign up to set email alerts
|

PROFILES OF Lyα EMISSION LINES OF THE EMITTERS ATz= 3.1

Abstract: We present the results of the observations of the Lyα line profiles of 91 emission-line galaxies at z = 3.1 with the spectral resolution of λ/δλ(FWHM) ≈ 1700, or 180 km s −1 . A significant fraction, ∼ 50% of the observed objects show the characteristic double peaks in their Lyα profile. The red peak is much stronger than the blue one for most of the cases. The red peaks themselves also show weak but significant asymmetry and their widths are correlated with the velocity separation of the red and the blue peak… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 43 publications
7
96
3
Order By: Relevance
“…We found this to be the best single value for achieving the highest S/N for the majority of LAEs in MUSE datacubes (HW17). Moreover, taking the instrumental resolution of MUSE into account, this value is also consistent with the expectations from the distributions of LAE FWHMs in the literature (e.g., Dawson et al 2007;Mallery et al 2012;Yamada et al 2012). Although the width of the spectral filter is optimised for LAEs, we emphasise that the resulting S/N of an Gaussian emission line decreases only as Fig.…”
Section: Cross-correlation With Matched Filtersupporting
confidence: 90%
“…We found this to be the best single value for achieving the highest S/N for the majority of LAEs in MUSE datacubes (HW17). Moreover, taking the instrumental resolution of MUSE into account, this value is also consistent with the expectations from the distributions of LAE FWHMs in the literature (e.g., Dawson et al 2007;Mallery et al 2012;Yamada et al 2012). Although the width of the spectral filter is optimised for LAEs, we emphasise that the resulting S/N of an Gaussian emission line decreases only as Fig.…”
Section: Cross-correlation With Matched Filtersupporting
confidence: 90%
“…In this case, even in the most extreme case of a purely external photoionizing source, a double peak similar to the observed peak would be produced (Cantalupo et al 2005;Verhamme et al 2015), so the answer is positive. Yamada et al (2012) observed 91 LAEs with a spectral resolution R 1700, very similar to that of MUSE. They show in their Fig.…”
Section: Two Other Probable Lyman Alpha Emitters At the Same Redshiftmentioning
confidence: 60%
“…5 the empirical relation between the velocity separation between the red and blue peaks and the FWHM of the stronger peak. Our LAE1 object has a rather small velocity separation (392±36 km s −1 ) for the width of the stronger (red) peak, sending its representative point onto the lower envelope defined by the objects of Yamada et al (2012). It is also reminiscent of the Lyman continuum emitters (LCEs) examined by Verhamme et al (2017).…”
Section: Two Other Probable Lyman Alpha Emitters At the Same Redshiftmentioning
confidence: 88%
“…A significant fraction of spectra also shows characteristic double peaks, with the red peak often being stronger than the blue (e.g. Tapken et al 2004Tapken et al , 2007Yamada et al 2012;Hong et al 2014;Henry et al 2015;Yang et al 2015). Interestingly, a high percentage of double peaked and asymmetric Lyα profiles appear well explained by the spherical symmetric scenarios mentioned above.…”
Section: Introductionmentioning
confidence: 94%